(untitled) (Research, Society and Development, 2021)
The radix entomolaris is an anatomical variation characterized by the presence of an additional root located in the distal-lingual region of mandibular molars. An accurate diagnosis is necessary to plan and institute effective endodontic therapy for teeth with this condition. The aim of this report was to present three cases of endodontic management in permanent mandibular first molars with radix entomolaris using contemporary technical resources. For diagnosis, periapical radiographs indicated the possibility of morphological alterations, which were confirmed in two cases by cone beam computed tomography (CBCT). Ultrasonic tips and magnification with operative microscopy were the auxiliary resources used for locating the root canals, which were prepared with NiTi rotary instrument systems and filled with gutta-percha by using the lateral condensation technique and AH Plus sealer. Resources such as periapical radiography, CBCT, magnification with operative microscopy, ultrasonic devices and NiTi instruments can be extremely valuable for use in the diagnosis and clinical approach to endodontic treatment of mandibular first molars with radix entomolaris.